Istikhdam Al-Dzaka' Al-Ishthina’i Chat Gpt Voice 'Au Gemini Voice Fi Ta’liim Maharat Al-Kalam Fi Al-Jamiat Al-Indonesia - Rahayu, Puji; Zamroni, Muh.; Anisatun, Dewi; Soleh, Moh. (UIN Maulana Malik Ibrahim Malang, 2025)
The use of Artificial Intelligence (AI) in the field of Education has attracted increasing attention in recent years. Through technology-based learning with a communicative approach, evaluation provides instant responses to help students improve their Arabic language independently. The application of AI in higher education can provide a more dynamic, interactive and responsive learning experience to students' needs in mastering Arabic, especially maharah kalam. This research is expected to provide new contributions to the literature on the use of AI in Arabic language learning, especially maharah kalam using Chat Gpt Voice and Gemini Voice in higher education. The results of this study are also expected to help improve the quality and accessibility of Arabic Language Education and open up new opportunities for the use of AI technology in the context of Education.